2009
DOI: 10.1051/0004-6361/200911971
|View full text |Cite
|
Sign up to set email alerts
|

The pulsations of the B5IVe star HD 181231 observed with CoRoT and ground-based spectroscopy

Abstract: Context. HD 181231 is a B5IVe star, which has been observed with the CoRoT satellite during ∼5 consecutive months and simultaneously from the ground in spectroscopy and spectropolarimetry. Aims. By analysing these data, we aim to detect and characterize as many pulsation frequencies as possible, to search for the presence of beating effects possibly at the origin of the Be phenomenon. Our results will also provide a basis for seismic modelling. Methods. The fundamental parameters of the star are determined fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 27 publications
(26 reference statements)
7
35
0
Order By: Relevance
“…They have been observed with the CoRoT photometric satellite (for a description of CoRoT, see Baglin et al 2006Baglin et al , 2009 during about five consecutive months and 27 consecutive days, respectively. A&A 539, A90 (2012) An analysis of their CoRoT light curves showed that several independent periods of variations are present in these stars, which we interpreted in terms of pulsation g-modes (Neiner et al 2009;Gutiérrez-Soto et al 2009). Late Be stars indeed exhibit pulsations of g-modes similar to those of slowly pulsating B (SPB) stars.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…They have been observed with the CoRoT photometric satellite (for a description of CoRoT, see Baglin et al 2006Baglin et al , 2009 during about five consecutive months and 27 consecutive days, respectively. A&A 539, A90 (2012) An analysis of their CoRoT light curves showed that several independent periods of variations are present in these stars, which we interpreted in terms of pulsation g-modes (Neiner et al 2009;Gutiérrez-Soto et al 2009). Late Be stars indeed exhibit pulsations of g-modes similar to those of slowly pulsating B (SPB) stars.…”
Section: Introductionmentioning
confidence: 78%
“…Assuming Ω Ωc = 0.9, as determined by Neiner et al (2009) andGutiérrez-Soto et al (2009). are summarized in Table 1. See also Table 3 of Neiner et al (2009).…”
Section: Hd 181231mentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable finding is the outburst signal detected in the B0.5IVe star HD 49330 (Huat et al 2009), a phenomenon that has not been observed to occur in any of the other observed Be stars, which are of later spectral type. Theoretical work is needed to understand and interpret the observed frequency patterns in the Be pulsators (Neiner et al 2009;Diago et al 2009;Gutiérrez-Soto et al 2009). Progress is hampered by the mathematical complexity of describing the oscillations in these flattened stars, induced by their rapid rotation, often close to their critical velocity.…”
Section: Introductionmentioning
confidence: 99%
“…The current theoretical models have difficulties in describing the pulsational characteristics of Be stars, due to the high rotational velocity of these objects. A brief description of the current knowledge of the pulsational behavior of Be stars can be found in Neiner et al (2009) and Emilio et al (in prep. ).…”
Section: Introductionmentioning
confidence: 99%